A Research on Common Fixed Point Theorems with Generalized Spaces: Exploring Fixed Point Theorems in Various Spaces (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present investigation is fundamentally worried about a few new sorts of fixed point theorems in various spaces, for example, cone metric spaces and fuzzy metric spaces. By utilizing these acquired fixed point theorems, we at that point demonstrate the presence and uniqueness of the solutions to two classes of two-point customary differential equation problems.